First-time mothers’ experiences of early labour in Italian maternity care services - Cappelletti, Giulia; Nespoli, Antonella; Fumagalli, Simona; Borrelli, Sara E. (Elsevier, 2016)
OBJECTIVE: The aim of this study is to explore first-time mothers' experiences of early labour in Italian maternity care services when admitted to hospital or advised to return home after maternity triage assessment. SETTING: The study was conducted in a second-level maternity hospital in northern Italy with an obstetric unit for both low- and high-risk women. PARTICIPANTS: The participants included 15 first-time mothers in good general health with spontaneous labour at term of a low-risk pregnancy who accessed maternity triage during early labour, and were either admitted to hospital or advised to return home. DESIGN: A qualitative interpretive phenomenological study was conducted. A face-to-face recorded semi-structured interview was conducted with each participant 48-72h after birth. FINDINGS: Four key themes emerged from the interviews: (a) recognising signs of early labour; (b) coping with pain at home; (c) seeking reassurance from healthcare professionals; and (d) being admitted to hospital versus returning home. Uncertainty about the progression of labour and the need for reassurance were cited by women as the main reasons for hospital visit in early labour. An ambivalent feeling was reported by the participants when admitted to hospital in early labour. In fact, while the women felt reassured in the first instance, some women subsequently felt dissatisfied due to the absence of one-to-one dedicated care during early labour. When advised to return home, a number of women reported feelings of disappointment, anger, fear, discouragement and anxiety about not being admitted to hospital; however, some of these women reported a subsequent feeling of comfort due to being at home and putting in place the suggestions made by the midwives during the maternity triage assessment. The guidance provided by midwives during triage assessment seemed to be the key factor influencing women׳s satisfaction when advised either to return home or to stay at the hospital during early labour. CONCLUSIONS AND IMPLICATIONS FOR PRACTICE: During antenatal classes and clinics, midwives should provide clear information and advice about early labour in order to increase women׳s confidence and self-efficacy, and decrease their anxiety and fear. During early labour, appropriate maternity care services should be offered according to individual needs. When home visits are not provided by midwives, a telephone triage run by midwives should be considered as a routine service for the first point of contact with women during early labour.